Turning Fantasy into Regulatory Reality: A New Approach to Daily Fantasy Sports Law - Feeney, Patrick (The Columbia Journal of Law & the Arts, 2016)
In Section I of this Note, I review the relevant literature and argue that the old moral and social externality arguments for banning or restricting fantasy sports do not hold up. While no particular path to regulation is the correct path, a comparative analysis of the functional structures of various speculative activities, and the legal and community control mechanisms apparent in each, provide some suggestions for what regulation should look like. In Sections II through V, I compare these speculative activities through four multidisciplinary lenses. In Section VI, I develop a recommended framework for legislation or regulation based on these comparisons and evaluate it against the laws recently implemented in New York and Massachusetts, the respective home states of FanDuel and DraftKings.